Comprehensive guide on organic and inorganic solar cells fundamental concepts to fabrication methods - Akhtaruzzaman, Md; Selvanathan, Vidhya (Academic Press, 2021)
Comprehensive Guide on Organic and Inorganic Solar Cells: Fundamental Concepts to Fabrication Methods is a one-stop, authoritative resource on all types of inorganic, organic and hybrid solar cells, including their theoretical background and the practical knowledge required for fabrication. With chapters rigorously dedicated to a particular type of solar cell, each subchapter takes a detailed look at synthesis recipes, deposition techniques, materials properties and their influence on solar cell performance, including advanced characterization methods with materials selection and experimental techniques. By addressing the evolution of solar cell technologies, second generation thin-film photovoltaics, organic solar cells, and finally, the latest hybrid organic-inorganic approaches, this book benefits students and researchers in solar cell technology to understand the similarities, differences, benefits and challenges of each device.